Towards equitable carbon responsibility: Integrating trade-related emissions and carbon sinks in urban decarbonization - Junliang Wu; Yafei Wang; Shuya Zhang; Yu Zhu; Bingyue Fu; Zhihui Zhang; Hanxi Chen; Shaoqing Chen (Environmental Science and Ecotechnology)
Cities play a pivotal role in global decarbonization, acting as a critical driver of carbon emissions. Accurately allocating carbon mitigation responsibility (CMR) is essential for designing effective and equitable climate policies. How cities manage carbon leakage across boundaries through supply chains and implement plan of increasing forest carbon sinks are important components for designing a fair and inclusive CMR. However, the combined impact of trade-related carbon leakage and forest carbon sinks on CMR allocation remains poorly understood. Here, we develop an integrated CMR allocation framework that accounts for both carbon leakage and variation of forest carbon offsets. When applied to the cities within the Guangdong–Hong Kong–Macao Greater Bay Area in China, it becomes evident that the inclusion of carbon leakage results in substantial alterations in mitigation quotas. Adjustments are observed to vary between ±10 % and 50 % across these cities from 2005 to 2020, a trend that is anticipated to continue until 2035. The redistribution of outsourced emissions through supply chains alleviates the mitigation burden on producer cities by 20–30 %. Additionally, accounting for carbon sinks substantially influences CMR allocation, particularly in forest-rich cities, which may see their carbon budgets increase by up to 10 %. Under an enhanced climate policy scenario, the growth rate of total mitigation quotas from 2025 to 2035 is projected to decrease by 40 % compared to a business-as-usual trajectory, reducing the burden on major producer cities. Our proposed CMR framework provides a robust basis for incentivizing coordinated mitigation efforts, promoting decarbonization in supply chains and enhancement of urban carbon sink capacities.